Effect of Au and/or Mo Doping on the Development of Carbon and Sulfur Tolerant Anodes for SOFCs—A Short Review - Niakolas, Dimitrios K.; Neofytidis, Charalambos S.; Neophytides, Stylianos G. (Frontiers in Environmental Science, 2017)
The presented work is a short review of the research attempts from our group with collaborators, during the last 15 years, which had as main objective to study and improve the electrocatalytic performance of Ni-based electrode materials for the CH4 Internal steam Reforming process (I.S.R.) in Solid Oxide Fuel Cells (SOFCs). In particular, NiO/YSZ and NiO/GDC anode powders were modified with Au and/or Mo nano-particles via different preparation methods. These efforts resulted in anode materials with high tolerance and improved electrocatalytic activity under both carbon forming and sulfur poisoning conditions. The most important findings are being reviewed and critical findings are being highlighted50 as to stress the key differences in the electrocatalytic performance between Ni/YSZ and Ni/GDC. The possible effects of Au and/or Mo addition on the physicochemical and strucutral properties of the cermets are thoroughly discussed as well as active functional layers in the form of anode SOFC electrodes.